Happiness as enterprise : an essay on neoliberal life - Binkley, Sam, 1963- (Albany : State University of New York Press, 2014)
"Examines the contemporary discourse on happiness through the lens of governmentality theory"--Provided by publisher.
Introduction: the new happiness -- An essay on neoliberal life -- The hinge of power -- To govern happily -- Happiness as potentiality -- How to be happy -- Positive psychology -- The emotional fold -- Horizons of policy -- The folding of happiness : a polemic -- When will I be happy? -- Time within time -- Happiness as generative temporality -- Risk and emotional life -- Growth, strength and the temporality of the living -- Habits of the happy -- Habitus of conduct -- Temporalization as intensification -- Convulsive temporalities -- The work of neoliberal governmentality -- The happiness of all and each -- A genealogy of happiness -- Pure obedience and reason of state -- Liberalism and the happiness of each -- Happiness as social life -- Interiorities of social government -- The event of happiness -- Disciplining interiority -- Intimacy as equilibrium -- Boredom and the durational habitus -- The alchemy of neoliberalism -- Governmentality and the emotional fold -- Neoliberalism as destructivist project -- Incentivizing intimacy -- And the sociabilities of neoliberalism -- Conclusion: against asphyxiation -- Bibliography.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Happiness; Self-culture.; Neoliberalism; Power (Social sciences); State, The; Happiness; Neoliberalism; Power (Social sciences); Self-culture.; State, The; PSYCHOLOGY / Social Psychology; Electronic books